Health Care Workers' Perceptions on Factors Affecting Diabetes Self-Management Among Type 2 Diabetes Mellitus Patients in Fiji: A Qualitative Study - Kumar, Lalesh; Mohammadnezhad, Masoud (Frontiers in Public Health, 2022)
Background Type 2 Diabetes Mellitus (T2DM) is known as a major cause of mortality globally. Diabetes self-management refers to daily activities undertaken to control or reduce the impact of diabetes on health and well-being to avoid further illness. Health Care Workers' (HCWs) can assist patients to be aware of self-care and solve the challenges diabetes presents. The management of diabetes can improve once HCWs promote measures that facilitate self-care activities by providing necessary information and supporting patients' initiatives to make lifestyle changes. This study aimed to explore HCWs perceptions on factors affecting diabetes self-management among T2DM patients of Fiji. Methods A qualitative study design was conducted to explore HCWs perceptions on factors affecting diabetes self-management using two Focus Group Discussions (FGDs) in Labasa, Fiji in 2021. The study settings were the Diabetic Hub Center, special outpatient department Labasa hospital and Nasea health Center Labasa. The study settings are located in an urban area. These health facilities provide special outpatient clinics to T2DM patients including clinics for other medical conditions. Nasea Health Center had 1,300 patients, the special outpatient's department Labasa hospital had 560 patients and the diabetic hub center Labasa had 295 patients at the time of the study. These patients either had T2DM or T2DM with other medical conditions. Purposive sampling was employed to recruit HCWs. The data were collected using an interview guide in semi-structured interviews and the interviews were audio recorded. The recorded data was transcribed verbatim and analyzed using thematic analysis process. Results The participants were 9 HCWs with age range of 25-49 years. A counselor, a medical officer, physiotherapist, nurses and dieticians were among the HCWs. Three major themes and seven sub themes were identified. These included Theme 1- “availability of services” with the sub themes of clinical services for T2DM and other support services available for T2DM patients. Theme 2- “barriers and challenges to diabetes self-management” with the sub themes of health system factors, socioeconomic factors and health system factors. Theme 3- “Needs for diabetes management” with the sub themes resources and skilled personnel. Conclusion The findings of this study demonstrate health system challenges such as lack of material resources and human resources compounded the factors affecting diabetes self-management. HCWs training as diabetes educators and developing policy on diabetes self-management are highly recommended to facilitate diabetes self-management.